Analisis Kemampuan Asesmen Guru Biologi Pra-Jabatan dalam Penyusunan Perencanaan Penilaian dan Instrumen Penilaian: Studi Deskriptif di Perguruan Tinggi - Zulhakim, Muthiah Khairunisa; Yuliana, Caesaria; Nugroho, Arosyid Wahyu; Arisyi, Reza; Ciptarsa, Cepi; Sulaimah, Umu; Asshiddiqi, Muhamad Hasbi; Septianto, Adi; Fitriani, Somariah (Universitas Negeri Padang, 2025)
This study aims to analyze the assessment skills of prospective biology teachers in developing assessment planning and qualitative test items. The method used is qualitative descriptive, with document analysis sheets and questionnaires as instruments. The study was conducted at a private university in Jakarta, involving 66 students using a saturated sampling technique. The results indicate that the prospective teachers' ability in “Developing Assessment Planning” falls under the “Good” category, while their ability in “Constructing Qualitative Test Items” is categorized as “Very Good.” The highest indicator in assessment planning is “Designing Assessments,” which is categorized as “Very Good” for meeting the minimum percentage criteria. The lowest indicator is “Formulating Competency Achievement Indicators,” which falls under the “Fair” category. The main challenge identified is the lack of understanding of biology assessment that is not yet fully aligned with the existing indicators. Thus, the implications of this study are significant in evaluating the competencies of prospective biology teachers in assessment development and planning. The findings can serve as a basis for developing more comprehensive assessment training programs, particularly to strengthen understanding in formulating competency achievement indicators and other areas needing improvement. Keywords: Assessment skills, prospective biology teachers, assessment planning.